2019
DOI: 10.1097/prs.0000000000005677
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous Bone Cranioplasty: Review of a 42-Year Experience by a Single Surgeon

Abstract: Background: Autogenous bone is frequently espoused as the gold standard material for cranioplasty procedures, yet alloplastic cranioplasty continues to persist in the search, presumably, for a simpler technique. Although short-term outcomes can be successful using foreign materials, long-term follow-up in these patients often demonstrates increased rates of failure because of exposure or late infection. Autogenous bone grafts, however, integrate and revascularize, and are thus more resistant to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…T otal scalp avulsions are significant injuries, most commonly secondary to long hair trapped in high-speed rotary machines. 1,3 Although variability in avulsion pattern exists, the avulsed plane is typically the loose areolar layer of the scalp. 1,2 Reconstruction of total scalp avulsion defects can be both complex and complicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T otal scalp avulsions are significant injuries, most commonly secondary to long hair trapped in high-speed rotary machines. 1,3 Although variability in avulsion pattern exists, the avulsed plane is typically the loose areolar layer of the scalp. 1,2 Reconstruction of total scalp avulsion defects can be both complex and complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous bone grafts, most commonly from adjacent areas of the cranium, the ribs, or the iliac crests, have several advantages including high growth potential and low infection rates. 1 However, donor site morbidity, especially in young children with few viable donor sites, is a major disadvantage. As a result, synthetic materials, such as polymethyl methacrylate or polyetheretherketone, have become the preferred option for many surgeons.…”
mentioning
confidence: 99%
“…Cranioplasty with autologous bone can be accomplished with either split grafts harvested at the time of reconstruction or replacement of the preserved craniectomy bone. Cabbad et al 9 recently reported a series of 153 cranioplasties accomplished with fresh split grafts. The outcomes reported, spanning four decades, are remarkable with zero complications.…”
Section: Introductionmentioning
confidence: 99%
“…High-energy injuries or pathological fractures, such as tumors and inflammation, are the main reasons for bone defects, which create numerous challenges in the clinical setting and require bone grafting (Campana et al, 2014;Hwang et al, 2017;Zhang H. et al, 2019). As the gold standard for bone substitution in clinical surgeries, the autogenous bone grafts application is limited by the inadequate practicability, donor-site morbidity, and complicated surgical procedures (Sharif et al, 2016;Bez et al, 2018;Cabbad et al, 2019;Chen et al, 2019). Consequently, a more valid alternative procedure of BTE platform was proposed.…”
Section: Introductionmentioning
confidence: 99%